PENGEMBANGAN WISATA BUKIT TARUWONGSO MENJADI TAMAN SATWA TARUWONGSO DENGAN PRINSIP ARSITEKTUR HIJAU DI SUKOHARJO - Ardi Winoto; Agung Kumoro Wahyuwibowo; Leny Pramesti (ARSITEKTURA, 2016)
Taruwongso is a tourist destination in Sukoharjo with major potential is wildlife and nature. However, in the absence of a manager, a lack of attention by people around, and visitors irresponsible, so many animals at Taruwongso hill who have lost their natural habitat.As the rescue efforts of wildlife and nature Taruwongso hill, the need for the development of Taruwongso hill travel into Taruwongso Animal Park that can accommodate a synergy between human behavior, animal behavior, and the behavior of nature in Sukoharjo.The problem of the design are: a synergy between human behavior, animal behavior, and the behavior of nature that will be contained greatly affect the shape Taruwongso Animal Park.Principles of Green Architecture is used as a basis for the synergy between human behavior, animal behavior, and the behavior of nature in Taruwongso Animal Park.The results obtained Animal Park is a design that can accommodate a synergy between human behavior, animal behavior, and the behavior of nature with the principles of Green Architecture. Keywords: Animal Park, Architecture,  Green Architecture, Taruwongso Hill.